Gut microbiome interacts with pregnancy hormone metabolites in gestational diabetes mellitus - Lyu, Xuejing; Wang, Shaona; Zhong, Jiaxin; Cai, Lingzhu; Zheng, Yanhui; Zhou, Ying; Zhou, Ying; Chen, Qionghua; Li, Qiyuan (Frontiers in Microbiology, 2023)
Change in the composition of intestinal microbiota is associated with metabolic disorders such as gestational diabetes mellitus (GDM). To understand how microbiota impacts the development of gestational diabetes mellitus, we profiled the intestinal microbiome of 54 pregnant women including 27 GDM patients. Each participant was sampled three times in the first trimester, the third trimester and postpartum. We evaluated the patterns of changing abundances of operational taxonomic units (OTU) between GDM and the healthy counterparts over the three timepoints. Based on the significant OTUs, we inferred 132 significantly altered metabolic pathways, and identified two overrepresented metabolites of pregnancy hormone, butyrate and mevalonate, as potential effectors of intestinal microbiota in GDM. Finally, we validated the impacts of the intestinal microbiota on GDM by demonstrating consistent changes of the serum levels of progesterone and estradiol and the urine levels of butyrate and mevalonate in an independent cohort. Our findings confirm that change in microbiota contributes to the onset of GDM by influencing the metabolism of pregnancy hormones, which provide a new, liver-intestine perspective on the pathogenesis of GDM with interpretable biomarkers for early diagnosis and prevention of the disease.